'New uses need old buildings': Gentrification aesthetics and the arts in Singapore. (February 2016) - Chang, TC
The phrases 'new uses need old buildings' and 'old buildings require new uses' emphasise the mutually reinforcing relationships between historic buildings and new activities in cities. What the phrases do not say are the challenges and incompatibilities that are part of the urban redevelopment process. Singapore's inner city has been transformed since the 1990s with the introduction of new economies. This paper focuses on one precinct that has undergone land use change – Little India. The concept of 'gentrification aesthetics' provides a suggestive frame to explore the form and outcome of urban change, as well as its contestations when new arts and cultural activities occupy historic buildings. Gentrification aesthetics as conceptualised in the West takes on different perspectives in Singapore, prompting questions on whether a 'Singapore style gentrification' is evolving – one that melds urban redevelopment with state ideology in arts enhancement and aesthetic regulation.